Plastic pollution in the Global South: Exploring social, behavioral, and structural factors - Voronkova, Anastasia; Richter, Isabel; Henderson, Lesley; Aruta, John Jamir Benzon R *; Dumbili, E.; Wyles, Kayleigh J.; Pahl, Sabine (Academic Press, 2023)
This chapter reviews plastic pollution in the context of the Global South with a particular focus on the social and behavioral science literature. We set the context by describing the problem of plastic globally and how the Global South is a focal point for environmental and human health impacts, before analyzing political and structural conditions of waste management in a few selected countries in Southeast Asia and Africa. Then, we review social and behavioral factors that contribute to plastic pollution, from social norms to religious and cultural aspects not typically considered. We summarize what is known about plastic pollution and human health with particular reference to waste pickers. We close by reviewing opportunities and challenges, giving positive examples of change, and highlighting research gaps.